Analysis Of Factors Influencing The Performance Of Posyandu Cadres In An Effort To Reduce Mmr And Imr In The Community Health Center Area Of Banjar District - Nur Laily; Fauzie Rahman; Nita Pujianti; Ayu Riana Sari Azwari; Anggun Wulandari; Endah Labati Silapurna; Aminah Rahmayanti; Shofa Yulia Rizki; Abdul Thalib (International Journal of Medical Toxicology and Legal Medicine, 2024)
Posyandu is a strategic step in developing the quality of Indonesia’s human resources to be able to build and help themselves. The lack of posyandu implementation has an indirect impact on the achievement of MMR and IMR, which cannot be separated from the role of cadres. The number of posyandu in South Kalimantan Province in 2023 was 4,013. Meanwhile, Banjar District has the highest number of inactive posyandu at 57 posyandu (61.29%) out of a total of 93 inactive posyandu in South Kalimantan Province. The percentage of active posyandu in Banjar District at 90.07% is the lowest and lower than the provincial average percentage of 98.25%. The current inactive posyandu indicates that the performance of the posyandu has not been optimized. According to Gibson (1996) performance can be determined by several influencing factors including individual factors, psychological factors and organizational factors. Meanwhile, according to Merwe (2008) performance is influenced by motivation, appreciation or reward, leadership and domicile. This study aims to analyze the factors that influence the performance of posyandu cadres. The method used in this study was analytical observational with a cross sectional approach with a sample size of 97 posyandu cadres in Banjar District. The sampling technique used purposive random sampling. The results showed that there was a relationship between training (p=0.0001) and there was no relationship between incentives (p=1.000), leadership (p=0.747) and domicile (p=0.798) with the performance of posyandu cadres in an effort to reduce MMR and IMR in the Banjar District Health Center working area. This study shows the importance of training in improving the performance of posyandu cadres and suggests that policies focus on increasing the capacity of posyandu cadres.